Optimal design of multistage centrifugal pump based on the combined energy loss model and computational fluid dynamics - Wang, Chuan (2016)
This paper proposes a method to optimize the design of a typical multistage centrifugal pump based on energy loss model and Computational Fluid Dynamics (ELM/CFD). Different grid numbers, turbulence models, convergence precisions, and surface roughness are calculated for a typical multistage centrifugal pump. External characteristic experiments are also conducted to benchmark the numerical simulation. Based on the results, the ELM/CFD method was established including various kinds of energy loss in the pump, such as disk friction loss, volumetric leakage loss, interstage leakage loss as well as the hydraulic loss, which occurred at inlet section, outlet section, impeller, diffuser and pump cavity, respectively. The interactive relationships among the different types of energy losses were systematically assessed. Applying suitable setting methods for numerical calculation renders more credible results, and ensuring the integrity of the calculation model is the key contributor to the accuracy of the results. The interstage leakage loss is converted by the disk friction loss; thus, they are positively correlated, that is, the disk friction loss can be reduced by decreasing the interstage leakage loss. Concurrently, the volumetric leakage loss is negatively correlated with the disk friction loss; thus, increasing the volumetric leakage loss can effectively reduce the disk friction loss. The increment of the volumetric leakage loss is greater than the decrement of the disk friction loss for general centrifugal pumps. This relationship between these types of losses, however, does not apply to pumps with significantly low specific speed. Therefore, reducing the volumetric leakage and interstage leakage losses is the most effective technique to increase the efficiency of general centrifugal pumps. The impeller should be designed according to the maximum flow design method, because the inevitable volumetric leakage loss will improve the pump efficiency under rated flow condition. Several methods have been proposed to improve the pump efficiency.